Temporal and Spatial Variations of Total Electron Content Enhancements During a Geomagnetic Storm on 27 and 28 September 2017. Issue 7 (14th July 2020) - Shinbori, Atsuki; Otsuka, Yuichi; Sori, Takuya; Tsugawa, Takuya; Nishioka, Michi
Abstract: Temporal and spatial evolutions of total electron content (TEC) and electron density in the ionosphere during a geomagnetic storm that occurred on 27 and 28 September 2017 have been investigated using global TEC data obtained from many Global Navigation Satellite System stations together with the ionosonde, geomagnetic field, Jicamarca incoherent scatter and Super Dual Auroral Radar Network (SuperDARN) radar data. Our analysis results show that a clear enhancement of the ratio of the TEC difference (rTEC) first occurs from noon to afternoon at high latitudes within 1 hr after a sudden increase and expansion of the high‐latitude convection and prompt penetration of the electric field to the equator associated with the southward excursion of the interplanetary magnetic field. Approximately 1–2 hr after the onset of the h m F 2 increase in the midlatitude and low‐latitude regions associated with the high‐latitude convection enhancement, the rTEC and f o F 2 values begin to increase and the enhanced rTEC region expands to low latitudes within 1–2 hr. This signature suggests that the ionospheric plasmas in the F 2 region move at a higher altitude due to local electric field drift, where the recombination rate is smaller, and that the electron density increases due to additional production at the lower altitude in the sunlit region. Later, another rTEC enhancement related to the equatorial ionization anomaly appears in the equatorial region approximately 1 hr after the prompt penetration of the electric field to the equator and expands to higher latitudes within 3–4 hr. Key Points: The midlatitude broad SED and SED plume are formed approximately 1–2 hr after a sudden enhancement of the high‐latitude convection The major cause of the midlatitude broad SED is due to an upward motion of the ionosphere by the enhanced convection electric field The EIA intensification occurs in the evening sector approximately 1 hr after the prompt penetration of the electric field to the equator